The Electrochemical Reaction Mechanism of Tin Phosphide with Sodium. Issue 7 (8th April 2016) - Zheng, Lituo; Dunlap, R. A.; Obrovac, M. N.
Abstract : The sodiation mechanism of Sn4 P3 was studied by ex-situ X-ray diffraction and Mössbauer effect spectroscopy. These results show that Sn4 P3 is initially amorphized during sodiation, and suggest that upon further sodiation both Sn and P react simultaneously with Na to form Na3 P, Na0.6 Sn, and Na4 Sn4 . Upon further sodiation, the Na-Sn phases react with Na to make Na5 Sn2 and Na15 Sn4 . These results are consistent with the behavior of Sn4 P3 in Li cells.